Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry. (1st May 2023) - Pang, Xu; Qiu, Jing; Zhang, Zhaoyang; Li, Pi; Xing, Jiangtao; Su, Xin; Liu, Guiqiao; Yu, Changyuan; Weng, Rui
Highlights: A multi-residue analysis method of 191 pesticides constructed. Modified QuEChERS method for pesticide extraction and purification from beef. C18 selectively removed lipids from the beef matrix. GC-orbitrap-MS for sensitive and reliable identification of pesticides. Validated method showed excellent sensitivity, linearity, accuracy and precision. Abstract: Increasing pesticide contamination in foods of animal origin has made the wide-scope multi-residue analysis of pesticides an international concern. By using 191 pesticides, this study investigates a sensitive and reliable method for multi-residue analysis of pesticides in beef to determine the extent of the application of this method. The QuEChERS method was employed to extract and purify the pesticides as C18 was utilized as the absorbents. Then, the purified pesticides were analysed using gas chromatography - quadrupole orbitrap mass spectrometry (GC-Q-Orbitrap-MS). The validation test results revealed that this method was satisfactorily sensitive since its screening detection limit (SDL) ranged from 0.2 to 100 µg∙kg −1 . The recovery tests implemented at three spiking levels, namely 100, 200, and 500 µg∙kg −1, generated the results of 71.95 %–113.97 %, while the intra- and inter-day precisions were 0.27 %–17.94 %, indicating that this method had excellent accuracy and precision.